Flexible perovskite photovoltaic device packaging material, preparation method and application thereof
By combining cover plate and film packaging method, the packaging materials are prepared using modified hollow glass microspheres and adhesives, which solves the instability problem of flexible perovskite photovoltaic devices, and achieves efficient water-oxygen barrier and good bending resistance, reducing costs.
Patent Information
- Application Number
- CN202411771237.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
Flexible perovskite photovoltaic devices are unstable when facing external factors such as water, oxygen, and stress. The existing packaging methods have problems such as poor water-oxygen barrier properties, insufficient bending resistance and wear resistance.
Using a method combining cover plate packaging method and film packaging method, the packaging material is prepared using hollow glass microspheres and adhesives. The surface modification and the formation of a hydrophobic lubricating layer are used to improve the bending resistance of the packaging material, and the water-oxygen barrier performance is enhanced through multi-layer packaging.
It significantly improves the fatigue resistance, wear resistance and bending resistance of flexible perovskite photovoltaic devices, reduces the use of adhesives, prevents device corrosion caused by aging and degradation, and reduces production costs.
Smart Images

Figure CN119614107A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of renewable energy, and specifically relates to a packaging material, a preparation method and an application of a flexible perovskite photovoltaic device. Background Art
[0002] As a new type of thin-film solar photovoltaic technology, perovskite photovoltaics has the advantages of low carbon production process, flexible devices, and good weak light effect, and is rapidly developing towards industrialization. However, perovskite materials have the characteristics of ionic crystals, so flexible perovskite photovoltaic devices still face instability problems caused by external factors such as water, oxygen, and stress. In order to ensure the long-term working stability of flexible perovskite photovoltaic devices and avoid corrosion, degradation and other damage to the devices caused by external factors, it is often necessary to encapsulate flexible perovskite photovoltaic devices to isolate them from external water and oxygen, and maintain a certain degree of bending resistance and wear resistance after encapsulation.
[0003] Currently, there are generally two main methods for encapsulating flexible perovskite photovoltaic devices, namely the cover method and the thin film method.
[0004] The cover method usually refers to tightly fitting a flexible cover (usually a polymer material cover) and an adhesive on the device to isolate the device from the external environment; the thin film method usually refers to the use of chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD) and other technologies to in-situ deposit a dense protective layer (usually inorganic films such as ceramics and silicon nitride) on the device surface to resist erosion from the environment.
[0005] However, the water and oxygen barrier properties of polymer materials are far from satisfactory. If the cover is too thin, it is difficult to form an effective water and oxygen barrier. If the cover is too thick, the bending resistance will be greatly reduced. In addition, the adhesive also has problems such as degradation products produced by aging and corrosion of devices. Thin film packaging uses expensive equipment, low raw material utilization, and long preparation time. If the film is too thick, its bending resistance is poor, and if the film is too thin, its wear resistance is poor.
[0006] Therefore, the two main methods generally used in the prior art for encapsulation of flexible perovskite photovoltaic devices have obvious defects. Summary of the invention
[0007] In view of the above technical problems, the primary purpose of the present invention is to provide a packaging process for a flexible perovskite photovoltaic device, which organically combines the cover packaging method and the thin film packaging method, and utilizes the self-lubricating property of the sphere to increase the anti-bending performance.
[0008] The second object of the present invention is to provide a packaging material for a perovskite cell, which is prepared by a surface grafting reaction.
[0009] The third object of the present invention is to provide an application of the perovskite battery packaging material in perovskite battery packaging, which plays an important role in improving the working stability of the perovskite battery.
[0010] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0011] 1. A packaging material for a flexible perovskite photovoltaic device:
[0012] The packaging material mainly consists of hollow glass microspheres and adhesives. The packaging material is prepared by using hollow glass microspheres made of inorganic substances, and the packaging material is used for packaging flexible devices.
[0013] The particle size and dimension of the hollow glass microspheres are 10-200 μm in diameter.
[0014] 2. A method for preparing a packaging material for a flexible perovskite photovoltaic device:
[0015] The method is to modify the surface of hollow glass microspheres with inorganic materials and then mix them into an adhesive to obtain the encapsulation material, which is used for the encapsulation of flexible devices.
[0016] The method specifically treats the surface of the hollow glass microspheres to promote the generation of hydroxyl dangling bonds or hydroxyl free radicals on the surface. The surface may be cleaned to generate hydroxyl dangling bonds or hydroxyl free radicals, then immersed in a dispersion to form a hydrophobic lubricating layer on the surface for modification, and then mixed into a thermal curing adhesive or an ultraviolet curing adhesive or a dual-curing adhesive to obtain the result.
[0017] The specific process of the method is:
[0018] 1) Plasma cleaning or UV-ozone cleaning of hollow glass microspheres with a diameter of 10-150 μm for 10-30 min to generate hydroxyl dangling bonds or hydroxyl free radicals on the surface, and then immersing in a polydimethylsiloxane dispersion with a concentration of 1wt%-10wt% for 5-10 min to form a hydrophobic lubricating layer on the surface of the glass microspheres;
[0019] 2) Weigh 0.1-1g of the modified hollow glass microspheres and mix them into 1-10g of epoxy resin adhesive or polyurethane adhesive, phenolic resin adhesive, silicone rubber adhesive, acrylic resin adhesive or other heat-curing adhesive or UV-curing adhesive, dual-curing adhesive, and stir evenly to form an adhesive mixed with glass microspheres.
[0020] Preferably, the PDMS in step 1 is replaced by other siloxanes (such as methyl silicone oil, modified silicone oil) or hydrophobic fatty hydrocarbons and mixtures thereof.
[0021] The packaging material is used in flexible device packaging.
[0022] Preferably, the flexible device is a flexible perovskite photovoltaic device.
[0023] 3. A packaging method of the packaging material, such as Figure 1 As shown, the method steps are:
[0024] Step 1: preparing the encapsulation material using hollow glass microspheres of inorganic matter;
[0025] Step 2: Coating the encapsulation material on the surface of the perovskite photovoltaic device;
[0026] Step 3: curing the encapsulation material on the surface of the perovskite photovoltaic device;
[0027] Step 4: Repeat the above steps 2-3 to perform multiple multi-layer packaging.
[0028] The perovskite photovoltaic device is a flexible device.
[0029] The step 2 is specifically as follows: coating the packaging material on the surface of the flexible perovskite photovoltaic device, and applying a pressure below 30 MPa above the packaging material and maintaining it for 1-10 minutes, so that the hollow glass microspheres in the packaging material are squeezed against each other under the action of external force and dispersed on the device surface through self-lubrication to form a uniform single-layer distributed glass microsphere layer.
[0030] The step 3 specifically involves curing the packaging material by heat treatment or ultraviolet treatment, so that the glass microsphere-adhesive layer is firmly fixed on the surface of the flexible device.
[0031] The step 4 is specifically to repeat the steps 2-3 multiple times on each surface of the device to perform multi-layer packaging. Specifically, the steps 2-3 can be repeated multiple times on the upper and lower surfaces of the device, and then the side of the device can be further packaged with the above-mentioned packaging materials, or with ordinary heat-curing adhesive, ultraviolet curing adhesive, or dual-curing adhesive according to specific circumstances.
[0032] The present invention utilizes packaging materials mainly composed of inorganic substances to be coated on the surface of flexible battery devices, rather than organic substances or rigid battery surfaces. Such treatment can significantly improve the original fatigue resistance, wear resistance and bending resistance of the flexible device.
[0033] The present invention organically combines the cover plate method and the thin film method, which can reduce the use of adhesives and is the most economical and effective method for encapsulating flexible perovskite photovoltaic devices.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] This method fully combines the advantages of glass microspheres' good water and oxygen barrier properties, fatigue resistance, high mechanical strength, and light-concentrating properties with the advantages of organic materials' bending resistance.
[0036] The encapsulation layer prepared in this project not only has excellent water and oxygen barrier properties, effectively preventing the degradation of the perovskite light-absorbing layer, but also has good fatigue resistance, wear resistance, and bending resistance. At the same time, it also greatly reduces the use of adhesives and reduces the corrosion of perovskite devices by aging decomposition products after long-term use of adhesives. In addition, this method does not require expensive equipment and materials, and can save costs to the greatest extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the technical process adopted by the present invention.
[0038] Figure 2 The initial photoelectric conversion efficiency of Examples 1-4, the photoelectric conversion efficiency after 100 days, and the percentage of efficiency decrease are shown.
[0039] Figure 3 The relationship between the photoelectric conversion efficiency and the number of bends of the batteries prepared in Examples 1-4 of the present invention and Comparative Examples 1-4.
[0040] Figure 4 1 is a comparison diagram of the JV curves of the batteries prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] It should be noted that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.
[0043] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0044] Embodiments of the present invention are as follows:
[0045] Example 1
[0046] Preparation of perovskite photovoltaic devices:
[0047] The Me-2PACz hole transport layer and FAPbI were assembled on the surface of a 20*20mm PET substrate coated with an ITO conductive layer. 3Perovskite light absorption layer 700nm, C60 electron transport layer 30nm, BCP blocking layer 7nm and 80nm silver electrode.
[0048] Device Package:
[0049] like Figure 1 As shown, 1g of hollow glass microspheres with a diameter of 120μm were weighed and treated in a plasma cleaner for 10min. After being taken out, they were dispersed in a dichloromethane solution of dimethyl silicone oil with a concentration of 1wt%. After stirring for 10min to fully react, the glass microspheres were filtered using a Buchner funnel. The microspheres were then mixed with 3g of UV-curable polyacrylate adhesive and stirred thoroughly to obtain a mixed adhesive. The mixed adhesive was drawn with a dropper and dripped onto the lower surface of the device (the back electrode side) to completely cover the lower surface of the device. The device was then placed on a hot press and a pressure of 5MPa was applied for 3min. The device was then taken out after being irradiated under a 365nm UV curing lamp for 5min. In the next step, the mixed adhesive was dripped onto the upper surface of the device (the conductive ITO substrate side) to completely cover the upper surface of the device. The device was then placed on a hot press and a pressure of 5MPa was applied for 3min. The device was then taken out after being irradiated under a 365nm UV curing lamp for 5min. The mixed adhesive was dripped onto the four sides of the device and irradiated under a 365nm UV curing lamp for 5 minutes to cure and seal the edges to complete the packaging.
[0050] Comparative Example 1
[0051] After the perovskite photovoltaic device is prepared in Example 1, it is packaged instead of using a PET cover. The process is as follows: absorb the UV-curing polyacrylate adhesive without adding glass microspheres and drip it on the lower surface of the device (the side of the back electrode) to completely cover the lower surface of the device, and then closely contact the PET cover with a thickness of 120μm with the adhesive and expel the bubbles, and then take out the device after irradiating it under a 365nm UV curing lamp for 5 minutes. The next step is to drip the UV-curing polyacrylate adhesive onto the upper surface of the device (the side of the conductive ITO substrate) to completely cover the upper surface of the device, and then closely contact the PET cover with a thickness of 120μm with the adhesive and expel the bubbles, and then take out the device after irradiating it under a 365nm UV curing lamp for 5 minutes. Add the above-mentioned UV-curing polyacrylate adhesive to the four sides of the device and irradiate it under a 365nm UV curing lamp for 5 minutes to cure and seal the edges to complete the encapsulation.
[0052] The JV curves of the batteries prepared in Example 1 and Comparative Example 1 are compared. Figure 4 As shown, due to the focusing effect of the glass microspheres, the initial efficiency of the battery prepared in Example 1 is higher than that of the battery prepared in Comparative Example 1.
[0053] Example 2
[0054] Preparation of perovskite photovoltaic devices:
[0055] The Me-4PACz hole transport layer and FAPbI were assembled on the surface of a 20*20mm PEN substrate coated with an ITO conductive layer. 3 The perovskite light absorption layer is 700nm, the PC61BM electron transport layer is 20nm, the BCP blocking layer is 7nm and the silver electrode is 80nm.
[0056] Device Package:
[0057] Weigh 1g of hollow glass microspheres with a diameter of 150μm and treat them in a plasma cleaner for 15min. Take them out and disperse them in a 1wt% 3-aminopropyltriethoxysilane (dissolved in isopropanol) solution. Stir for 10min to fully react. Filter the glass microspheres with a Buchner funnel, mix them with 4g of heat-curing bisphenol A epoxy resin adhesive and stir them fully to obtain a mixed adhesive. Use a dropper to draw the mixed adhesive and drop it on the lower surface of the device (back electrode side) to completely cover the lower surface of the device. Then place the device on a hot press, apply 3MPa pressure for 2min, raise the hot press temperature to 100℃, and take out the device after heat curing for 5min. Add the mixed adhesive to the upper surface of the device (conductive ITO substrate side) to completely cover the upper surface of the device. Then place the device on a hot press, apply 3MPa pressure for 2min, raise the hot press temperature to 100℃, and take out the device after heat curing for 5min. Add the mixed adhesive to the four sides of the device and heat at 100°C for 5 minutes to cure and seal the edges.
[0058] Comparative Example 2
[0059] After the perovskite photovoltaic device is prepared in Example 2, it is packaged instead of using a PET cover. The process is as follows: absorb the heat-curing bisphenol A epoxy resin adhesive without adding glass microspheres and drip it on the lower surface of the device (the side of the back electrode) to completely cover the lower surface of the device, and then closely contact the PET cover with a thickness of 150μm with the adhesive and expel the bubbles, and then take out the device after heat curing at 100°C for 5min. The next step is to drip the heat-curing bisphenol A epoxy resin adhesive onto the upper surface of the device (the side of the conductive ITO substrate) to completely cover the upper surface of the device, and then closely contact the PET cover with a thickness of 150μm with the adhesive and expel the bubbles, and then take out the device after heat curing at 100°C for 5min. Add the above-mentioned heat-curing bisphenol A epoxy resin adhesive to the four sides of the device and heat at 100°C for 5min to cure and seal the edges to complete the encapsulation.
[0060] Example 3
[0061] Preparation of perovskite photovoltaic devices:
[0062] The MeO-2PACz hole transport layer, FA 0.9 Cs 0.1 PbI 3 The perovskite light absorption layer is 750nm, the PC61BM electron transport layer is 20nm, the BCP blocking layer is 7nm and the silver electrode is 80nm.
[0063] Device Package:
[0064] Weigh 2g of hollow glass microspheres with a diameter of 80μm and treat them in a plasma cleaner for 15min. Take them out and disperse them in a hexafluorobutyl triethoxysilane solution (solvent ethanol) with a concentration of 1wt%. After stirring for 10min to fully react, filter the glass microspheres with a Buchner funnel, mix them with 6g of polybutadiene epoxy resin and stir them thoroughly to obtain a mixed adhesive. Use a dropper to draw the mixed adhesive and drop it on the lower surface of the device (the back electrode side) to completely cover the lower surface of the device. Then place the device on a hot press and apply a 6MPa pressure for 5min. Raise the hot press temperature to 110℃ and keep it for 5min before taking out the device. Add the mixed adhesive to the upper surface of the device (the conductive ITO substrate side) so that the upper surface of the device is completely covered. Then place the device on a hot press and apply a 6MPa pressure for 5min. Raise the hot press temperature to 110℃ and keep it for 5min before taking out the device. Add the mixed adhesive to the four sides of the device and heat it at 110℃ for 5min to cure the edge seal.
[0065] Comparative Example 3
[0066] After the perovskite photovoltaic device obtained in Example 3 is prepared, a PI cover is used instead for encapsulation. The process is as follows: a polybutadiene epoxy resin adhesive without glass microspheres is absorbed and dripped on the lower surface of the device (the back electrode side) to completely cover the lower surface of the device, and then a PI cover with a thickness of 80 μm is in close contact with the adhesive and the bubbles are discharged, and then the device is taken out after heat curing at 110 ° C for 5 minutes. The next step is to drop the polybutadiene epoxy resin adhesive onto the upper surface of the device (the conductive ITO substrate side) to completely cover the upper surface of the device, and then a PI cover with a thickness of 80 μm is in close contact with the adhesive and the bubbles are discharged, and then the device is taken out after heat curing at 110 ° C for 5 minutes. The above-mentioned polybutadiene epoxy resin adhesive is dripped on the four sides of the device and heated at 110 ° C for 5 minutes to cure and seal the edges to complete the encapsulation.
[0067] Example 4
[0068] Preparation of perovskite photovoltaic devices:
[0069] The MeO-4PACz hole transport layer, FA 0.95 Cs0.05 PbI 3 The perovskite light absorption layer is 750nm, the evaporated C60 electron transport layer is 30nm, the BCP is 7.5nm and the silver electrode is 90nm.
[0070] Device Package:
[0071] Weigh 1.5g of hollow glass microspheres with a diameter of 60μm and treat them in a plasma cleaner for 20min. After taking them out, disperse them in a vinyl trimethoxysilane (solvent dichloromethane) solution with a concentration of 1.5wt%. After stirring for 15min to fully react, use a Buchner funnel to filter the glass microspheres, mix them with 4g of silicone rubber and stir them thoroughly to obtain a mixed adhesive. Use a dropper to absorb the mixed adhesive and add it to the lower surface of the device (the back electrode side) to completely cover the lower surface of the device. Then place the device on a hot press and apply 8MPa pressure for 4min. Raise the hot pressing temperature to 105℃ and keep it for 10min before taking out the device. Add the mixed adhesive to the upper surface of the device (the conductive ITO substrate side) so that the upper surface of the device is completely covered. Then place the device on a hot press and apply 8MPa pressure for 4min. Raise the hot pressing temperature to 105℃ and keep it for 10min before taking out the device. Add the mixed adhesive to the four sides of the device and cure and seal the edges at 105℃.
[0072] Comparative Example 4
[0073] On the photovoltaic device prepared in Example 4, a PI cover plate is used for encapsulation. The process is as follows: the silicone rubber adhesive without glass microspheres is absorbed and dripped on the lower surface of the device (the back electrode side) to completely cover the lower surface of the device, and then the PI cover plate with a thickness of 60μm is in close contact with the adhesive and the bubbles are discharged, and then the device is taken out after heat curing at 105°C for 5min. In the next step, the silicone rubber adhesive is dripped onto the upper surface of the device (the conductive ITO substrate side) to completely cover the upper surface of the device, and then the PI cover plate with a thickness of 60μm is in close contact with the adhesive and the bubbles are discharged, and then the device is taken out after heat curing at 105°C for 5min. The above-mentioned silicone rubber adhesive is dripped on the four sides of the device and heated at 105°C for 5min to cure and seal the edges to complete the encapsulation.
[0074] The initial photoelectric conversion efficiency of the above examples 1-4 and the photoelectric conversion efficiency after 100 days and the percentage of efficiency decline are as follows: Figure 2As shown in the figure, it can be seen that the battery efficiencies prepared in Examples 1-4 are 20.44%, 20.81%, 20.23%, and 20.90%, respectively. After 100 days of continuous operation, the efficiencies are 20.05%, 20.06%, 20.14%, and 20.35%, respectively. The percentage decreases are 1.9%, 3.6%, 0.42%, and 2.62%, respectively. The battery efficiency decreases by no more than 4%, indicating that the packaging method of the present invention has strong reliability and effectiveness.
[0075] The relationship between the photoelectric conversion efficiency and the number of bends of the batteries prepared in the above Examples 1-4 and Comparative Examples 1-4 is as follows: Figure 3 As shown in the figure, it can be seen that the batteries prepared in Examples 1-4 still maintain more than 89% of the initial efficiency after being bent 10,000 times, while the batteries prepared in Comparative Examples 1-4 suddenly fail due to physical damage after being bent 6,000 times.
[0076] After testing, the bending radius of the batteries prepared in Examples 1-4 and Comparative Examples 1-4 can reach 5 mm, but the bending times of the batteries prepared in Examples 1-4 are significantly more than those in Comparative Examples 1-4.
[0077] Through the above implementation comparison, it can be seen that the scheme of the present invention combines the characteristics of glass microspheres with good water and oxygen barrier properties, high mechanical strength, and light-focusing effect and the advantage of organic materials' resistance to bending, and assembles organic-inorganic composite packaging materials on the surface of flexible perovskite photovoltaic devices based on the self-lubricating principle of glass microspheres.
[0078] The flexible device encapsulation layer prepared by the method not only has excellent water and oxygen barrier properties, improves the long-term working stability of photovoltaic devices, but also has good wear resistance and bending resistance. At the same time, it also greatly reduces the use of adhesives, preventing the corrosion of devices and the decline of encapsulation effect caused by aging and degradation of organic adhesives after long-term use. In addition, the method does not require expensive equipment and materials, can save costs to the greatest extent, and is conducive to reducing costs and increasing efficiency of perovskite photovoltaic devices.
Claims
1. A packaging material for a flexible perovskite photovoltaic device, characterized in that: The packaging material mainly consists of hollow glass microspheres and adhesives. The packaging material is prepared by using hollow glass microspheres made of inorganic substances, and the packaging material is used for packaging flexible devices.
2. The packaging material for a flexible perovskite photovoltaic device according to claim 1, characterized in that: The particle size and diameter of the hollow glass microspheres are 10-150 μm.
3. A method for preparing a packaging material for a flexible perovskite photovoltaic device according to claim 1, characterized in that: The method is to modify the surface of hollow glass microspheres with inorganic materials and then mix them into an adhesive to obtain the encapsulation material, which is used for the encapsulation of flexible devices.
4. The preparation method according to claim 3, characterized in that: The method specifically treats the surface of the hollow glass microspheres to induce the generation of hydroxyl dangling bonds or hydroxyl free radicals on the surface, then immerses the microspheres in a dispersion to form a hydrophobic lubricating layer on the surface for modification, and then mixes the microspheres into a heat-curing adhesive or an ultraviolet-curing adhesive or a dual-curing adhesive to obtain the microspheres.
5. The preparation method according to claim 3, characterized in that: The specific process of the method is: 1) The hollow glass microspheres are subjected to plasma cleaning or UV-ozone cleaning for 10-30 minutes to generate hydroxyl dangling bonds or hydroxyl free radicals on the surface, and then immersed in a polydimethylsiloxane dispersion with a concentration of 1wt%-10wt% for 5-10 minutes to form a hydrophobic lubricating layer on the surface of the glass microspheres; 2) Weigh 0.1-1g of the modified hollow glass microspheres and mix them into 1-10g of epoxy resin adhesive or polyurethane adhesive, phenolic resin adhesive, silicone rubber adhesive, acrylic resin adhesive or other heat-curing adhesive or UV-curing adhesive, dual-curing adhesive, and stir evenly.
6. An application of the packaging material according to any one of claims 1 to 2 or the packaging material prepared by the preparation method according to claims 3 to 5, characterized in that: Application in flexible device packaging.
7. A packaging method for the packaging material according to any one of claims 1 to 2 or the packaging material prepared by the preparation method according to claims 3 to 5, characterized in that: The steps are as follows: Step 1: preparing the encapsulation material using hollow glass microspheres of inorganic matter; Step 2: Coating the encapsulation material on the surface of the perovskite photovoltaic device; Step 3: curing the encapsulation material on the surface of the perovskite photovoltaic device; Step 4: Repeat the above steps 2-3 to perform multiple multi-layer packaging.
8. The packaging method of a flexible perovskite photovoltaic device according to claim 7, characterized in that: The step 2 is specifically as follows: coating the packaging material on the surface of the perovskite photovoltaic device, and applying a pressure below 30 MPa above the packaging material and maintaining it for 1-10 minutes, so that the hollow glass microspheres in the packaging material are squeezed against each other under the action of external force and dispersed on the device surface through self-lubrication to form a uniform single-layer distributed glass microsphere layer.
9. The packaging method of a flexible perovskite photovoltaic device according to claim 7, characterized in that: The step 3 specifically involves curing the packaging material by heat treatment or ultraviolet treatment.
10. A packaging method for a flexible perovskite photovoltaic device according to claim 7, characterized in that: The step 4 specifically repeats steps 2-3 multiple times on each surface of the device to perform multi-layer packaging.